Islam Political Construction in Indonesia’s Foreign Policy - Halim, Abdul; Nisrina, Athira; Hafizh Ahmad Bayurizki (Andalas Institute of International Studies, 2025)
Since the beginning of independence, Indonesia's Islamic identity has played an important role, especially in efforts to gain recognition from other countries. This research aims to find out how the construction of Islamic Identity in Indonesia's foreign policy making from the Soekarno to Jokowi administration. This research uses qualitative research methods by taking constructivism theory as an analytical knife. The results show that Islamic identity has an important role in Indonesia's foreign policy, especially in the era of President Soekarno, Megawati, and SBY. Meanwhile, during the reigns of Soekarno, Habibie and Gus Dur, Islamic identity still played an important role, although it did not have a significant influence on foreign policy.